2020
DOI: 10.3389/fcimb.2020.578098
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology and Risk Factors of Clostridium difficile ST81 Infection in a Teaching Hospital in Eastern China

Abstract: BackgroundThe prevalence of Clostridium difficile causes an increased morbidity and mortality of inpatients, especially in Europe and North America, while data on C. difficile infection (CDI) are limited in China.MethodsFrom September 2014 to August 2019, 562 C. difficile isolates were collected from patients and screened for toxin genes. Multilocus sequence typing (MLST) and antimicrobial susceptibility tests by E-test and agar dilution method were performed. A case group composed of patients infected with se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Previous studies comparing patients with and without underlying chronic kidney disease (CKD) noted that the former had a higher risk of initial and recurrent episodes of CDI [20,21]. Similarly, these findings were supported by a recent study that observed an almost fourfold increased risk (OR:3.68, CI: 1.63-8.31, p = 0.002) of developing CDI in patients with underlying CKD [22]. The reduced function of the kidney not only interferes with the elimination of the toxins from the body but also alters the functions of the intestinal microbiota and PLOS GLOBAL PUBLIC HEALTH activates systemic inflammation [23][24][25].…”
Section: Discussionmentioning
confidence: 58%
“…Previous studies comparing patients with and without underlying chronic kidney disease (CKD) noted that the former had a higher risk of initial and recurrent episodes of CDI [20,21]. Similarly, these findings were supported by a recent study that observed an almost fourfold increased risk (OR:3.68, CI: 1.63-8.31, p = 0.002) of developing CDI in patients with underlying CKD [22]. The reduced function of the kidney not only interferes with the elimination of the toxins from the body but also alters the functions of the intestinal microbiota and PLOS GLOBAL PUBLIC HEALTH activates systemic inflammation [23][24][25].…”
Section: Discussionmentioning
confidence: 58%
“…In Asia, the tcdA – tcdB + C. difficile strain ribotype 017/ST37 was previously reported to be the most epidemic clone ( Tang et al, 2016 ; Imwattana et al, 2019 ). Recently, however, numerous studies have demonstrated that another tcdA – tcdB + strain, ST81, has emerged as the predominant clone in northern and eastern China ( Qin et al, 2017 ; Cui et al, 2019 ; Cheng et al, 2020 ; Yang et al, 2020 ). In accordance with this, in our follow-up monitoring, the prevalence of ST81 was found to be remarkably higher than that of ST37 compared with our previous findings at the same institution in Shanghai ( Dong et al, 2014b ).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review in 2016 demonstrated that ST37, a tcdA -negative and tcdB -positive (A – B + ) strain, was most prevalent in mainland China ( Tang et al, 2016 ). However, several recent studies in Beijing and Shanghai found that the epidemic clone had been replaced by another tcdA -negative and tcdB -positive strain, ST81 ( Qin et al, 2017 ; Cui et al, 2019 ; Cheng et al, 2020 ; Yang et al, 2020 ), which has caused multiple nosocomial outbreaks. Isolates of C. difficile have been classified into five distinct phylogenetic lineages ( Janezic and Rupnik, 2015 ) based on the MLST database, where ST81 and ST37 belong to clade 4 and mainly correspond to ribotype 017 ( Wu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%